证明:1^2 3^2 5^2 (2k-1)^2=1/3k(4k^2-1)

来源:学生作业帮助网 编辑:作业帮 时间:2024/05/09 09:23:08
证明:1^2 3^2 5^2 (2k-1)^2=1/3k(4k^2-1)

证明:1^2 3^2 5^2 (2k-1)^2=1/3k(4k^2-1)
证明:1^2 3^2 5^2 (2k-1)^2=1/3k(4k^2-1)

证明:1^2 3^2 5^2 (2k-1)^2=1/3k(4k^2-1)
归纳法:
(1)当n=1时 左边等于1右边等于1/3*1*(4*1^2-1)=1
(2)假设当k=n时 等式成立 则1^2+3^2+5^2+(2k-1)^2=1/3k(4k^2-1)
则当n=k+1时
(2k+1)^2+1/3*k*(4k^2-1) =(2k+1)^2+1/3*k(2k+1)(2k-1)
=(2k+1)(5/3k+1+2/3k^)
=1/3(2k+1)(2k^+5k+3) =1/3(2k+1)(k+1)(2k+3)
=1/3(k+1)(4k^2+8k+3)
=1/3(k+1)[4(k+1)^2-1]
由(1)(2)得 成立了 !

应该是证明:1^2+3^2+5^2+......+(2k-1)^2=1/3k(4k^2-1)
(2k-1)^2=4k^2-4k+1(分解成这样)
所以1^2+3^2+5^2+......+(2k-1)^2
=4(1^2+2^2+3^2+......+k^2)-4(1+2+3+.....+k)+k
=4k(k+1)(2k+1)/6-4k(k+1)/2+k,(对这项化简既得答案)
=1/3k(4k^2-1)